Expressão, purificação e caracterização de proteínas dos fitovírus SBMV e RSPaV - Mariutti, Ricardo Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The grapevine culture is the most economically important fruit plant in the world. The grapevine is the basic source of high valued wines and other alcoholic beverages. The Rupestris stem pitting associated virus-RSPaV was identified as the causative agent of the rupestris stem pitting (RSP) disease, a component ofthe the rugose wood (RW) complex, one of the major disease complexes affecting grapevines. This disease is transmitted by grafting and is one of the most widespread viruses of grapevine in the world. In brazil this disease was reported for the first time in late 1960s. As it is difficult to seperate the viral particles from the infected plant, the expression of large-scale of coat protein of RSPaV in bacteria is a promising strategy for understanding their properties. The bean crop productivity has also greatly affected by the occurrence of diseases that reduce the production and consequently reduce their supply, causing an increasein the prices. This virus has a narrow host range, confined almost exclusively to species of leguminous species, some of the species has a very high economical value such as the common bean and soybean. The movement protein (MP), serine protease and VPg, are produced in low concentrations, making impossible the large-scale purification from infected plants. In Brazil, more than ten virus were reported in beans, among them, Southern bean mosaic virus (SBMV) from the genus Sobemovirus. The large scale expression and purification of proteins VPg, serine protease and movement protein of SBMV and capisidial protein of RSPaV were performed using pMAL pET28a vectors. Analysis of the proteins by dynamic light scattering showed that was possible to obtain monomodal protein solutions. By circular dichroism was observed that the proteins were structured and the investigation of protein-ligand interactions was performed using nuclear magnetic resonance. These results contributed to increase the knowledge...

A videira é a frutífera economicamente mais importante no mundo e é cultivada para que seus frutos produzam uvas de mesa, suco, e uvas passas. As bagas da videira são também a base para o alto valor agregado dos vinhos e outras bebidas alcoólicas. O Rupestris stem pitting associated virus - RSPaV foi identificado como o agente causador da doença do lenho estriado ou cascudo (Rupestris stem pitting - RSP), um dos componentes do complexo do lenho rugoso da videira (Rugose wood - RW). Esta doença é transmitida por enxertia e constitui uma das viroses de videira mais disseminadas no mundo, sendo descrita no Brasil no final dos anos 60. Devido à dificuldade de purificação das partículas virais a partir da videira infectada, a expressão em larga escala da proteína capisidial do RSPaV em bactérias é uma estratégia promissora para o entendimento de suas propriedades. A cultura do feijão também tem produtividade grandemente afetada pela ocorrência de doenças que diminuem a produção e, conseqüentemente, reduzem a sua oferta, provocando um aumento nos preços de mercado. No Brasil, foram descritas mais de dez viroses em feijoeiro, citando-se aquela causada pelo Southern bean mosaic virus (SBMV) do gênero Sobemovirus. Este vírus tem uma restrita gama de hospedeiras, confinada quase exclusivamente a espécies da família das leguminosas, sendo algumas de interesse econômico como o feijoeiro comum e a soja. As proteínas do movimento (MP), serino protease e VPg, são produzidas em baixas concentrações, impossibilitando a purificação em larga escala a partir de plantas infectadas. A expressão e purificação em larga escala das proteínas VPg, serino protease e proteína do movimento do SBMV e proteína capisidial do RSPaV, foram realizadas utlizando os vetores pET28a e pMAL. Análises das proteínas, através de espalhamento dinâmico de luz mostraram que foi possível obter soluções proteicas monomodais...
Keywords: Fitopatologia; Virus de plantas; Videira; Proteínas virais - Purificação